Cytokines in the Cerebrospinal Fluids of Patients with Chronic Fatigue Syndrome/Myalgic Encephalomyelitis - D. Peterson; E. W. Brenu; G. Gottschalk; S. Ramos; T. Nguyen; D. Staines; S. Marshall-Gradisnik (Hindawi Limited, 2015)
Objectives. Previous research has provided evidence for dysregulation in peripheral cytokines in patients with Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME). To date only one study has examined cytokines in cerebrospinal fluid (CSF) samples of CFS/ME patients. The purpose of this pilot study was to examine the role of cytokines in CSF of CFS/ME patients. Methods. CSF was collected from 18 CFS/ME patients and 5 healthy controls. The CSF samples were examined for the expression of 27 cytokines (interleukin- (IL-) 1β, IL-1ra, IL-2, IL-4, IL-6, IL-7, IL-8, IL-9, IL-10, IL-12p70, IL-13, IL-15, IL-17, basic FGF, eotaxin, G-CSF, GM-CSF, IFN-γ, IP-10, MCP-1 (MCAF), MIP-1α, MIP-1β, PDGF-BB, RANTES, TNF-α, and VEGF) using the Bio-Plex Human Cytokine 27-plex Assay. Results. Of the 27 cytokines examined, only IL-10 was significantly reduced in the CFS/ME patients in comparison to the controls. Conclusions. This preliminary investigation suggests that perturbations in inflammatory cytokines in the CSF of CFS/ME patients may contribute to the neurological discrepancies observed in CFS/ME.